ANALISIS EFISIENSI PENGELOLAAN TEMPAT TIDUR RUMAH SAKIT BERDASARKAN GRAFIK BARBER JOHNSON DI RS PKU MUHAMMADIYAH YOGYAKARTA TAHUN 2015 - Maya Nanda Dewi; Adesti Ratna Pratiwi (MEDIA ILMU KESEHATAN, 2016)
Background: Hospital Statistic can be applied as a measurement tool of service quality by the hospital and as a concern for decision-making. Barber Johnson Graphic (BJG) can be used as an information source in decision-making process. Barber Johnson indicators are BOR, LOS, TOI, BTO to measure beds utilization efficiency. RS PKU Muhammadiyah Yogyakarta has employed computerized Barber Johnson Graphic, however, in 2015 the graphics did not indicate efficiency. Objective: To analyze the efficiency of beds management based on BJG in RS PKU Muhammadiyah Yogyakarta in 2015. Methods: This study was descriptive qualitative with cross sectional approach. Result: RS PKU Muhammadiyah Yogyakarta has been using computerized system to collect and process data of daily inpatient census, and to present hospital indicators with BJG. Based on BJG comparison between wards, it showed that Arafah ward presented efficient area with the value of hospital indicators were BOR= 76.14%, LOS= 5.02, TOI= 1,57, and BTO= 55,38. Whereas the least efficient area is showed by IMC ward with the value of hospital indicators were BOR= 46.81%, LOS= 14.59, TOI=16.57, and BTO= 11,71. Conclusion: Beds management in RS PKU Muhammadiyah Yogyakarta has employed computerized system. BJG showed that Arafah ward was the most efficient ward in bed management, and IMC is the least efficient in bed management. Keywords: Efficiency, Beds Management, Barber Johnson Graphic.